2005
DOI: 10.1590/s0365-05962005001000007
|View full text |Cite
|
Sign up to set email alerts
|

Positividade sorológica antiPGL-I em contatos domiciliares e peridomiciliares de hanseníase em área urbana

Abstract: Resumo: FUNDAMENTOS -Pesquisas atuais buscam avaliar a prevalência de pessoas infectadas pelo M. leprae, bem como o valor preditivo dos testes utilizados, em meio aos quais está a sorologia, que detecta anticorpos contra um antígeno específico da parede do Mycobacterium leprae, o glicolipídio fenólico (PGL-I). OBJETIVOS -Conhecer a taxa de infecção em contatos intra e peridomiciliares, e a relação de soropositividade com sexo, idade e grupo multibacilar/paucibacilar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
6
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
4
6
1
2
Order By: Relevance
“…Seropositivity was higher in contacts aged over 15 years-old. This is in agreement with data obtained by Calado 10 . Other authors have shown no differences 28 in seropositivity among age groups, or that it diminished 30 or increased 29 with age.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Seropositivity was higher in contacts aged over 15 years-old. This is in agreement with data obtained by Calado 10 . Other authors have shown no differences 28 in seropositivity among age groups, or that it diminished 30 or increased 29 with age.…”
Section: Resultssupporting
confidence: 94%
“…No consensus exists in the literature regarding these data. Some reports showed higher positivity among females 12 17 29 30 28 , while others showed no difference between males and females 10 23 2 28 4 26 . Association with the leprosy index case showed that higher seropositivity occurred among household contacts of multibacillary cases of leprosy (23.9%, p-value <0.001).…”
Section: Resultsmentioning
confidence: 96%
“…The proportion of seropositivity among contacts with a MB index case (22.6%) in this study was higher than that (18.4%) shown by Calado et al 4 . A study of the ML Flow test that included contacts conducted by Bührer-Sékula et al 3 made no mention of index cases.…”
contrasting
confidence: 83%
“…The majority of cases were PB, which is typical for this age group 5 7 12 18 . The percentage of seropositivity (19.7%) observed among the contacts of this study falls between those obtained in Bührer-Sékula et al 3 and Calado et al 4 , which were 28.6% and 15.6%, respectively. The Bührer-Sékula et al 3 study involved 42 household contacts and made no reference to the age of the individuals.…”
supporting
confidence: 72%
“…10 Another important indicator among the patients was the percentage of leprosy cases with household contacts (46.4%), 44.9% of them presenting a seropositive ML Flow test result. Other authors reinforce the necessity of detailed dermatoneurological examination of household contacts 5 , since, in Brazil, only a part of these contacts are examined 2 6 . Use of the ML Flow test helped the improve the diagnosis of suspected leprosy cases, since it is not yet part of the service routine, rather it provides support in the operational process of diagnosis aimed at reducing endemy in the district.…”
Section: Discussionmentioning
confidence: 91%